Factors Affecting Birth Weight: A Study in A Secondary Level Hospital in Gas Affected Area of Bhopal - Joshi, Sheloj M.; Likhar, S K; Athavale, A V; Shukla, U.S. (National Journal of Community Medicine, 2013)
Background: Birth weight is an alarming indicator to judge the survival chances of the new-born. Many of the new-borns die during their first year of life because of low birth weight as they become the victims of protein energy malnutrition and infection. Objectives: The study was conducted with an objective to measure the frequency of low birth weight (LBW) at a Secondary level hospital in Bhopal city and to find the determinants of low birth weight like maternal age, parity, gestational age, anaemia, sex of baby etc. Material & method: As a retrospective analytical study, obstetric records of all women who delivered in the Indira Gandhi Mahila Evem Balya Chikitsalaya, Gas Rahat, Bhopal over a period of two months i.e. September and October 2012 were examined. Statistical analysis: Data was analysed using SPSS version 20 statistical software. Chi square test was applied as a test of significance. Result: Out of the 441 new-borns included in the study, 242 (54.9%) were males and 199 (45.1%) were females. Out of 441, 52 new-borns (11.8%) had birth weight of less than 2.5 kg.. The period of gestation (POG) of mother was significantly associated with birth weight. Anaemia in mother, parity of mother, maternal age and Sex of the baby were not significantly associated with birth weight of the baby. Conclusion: As far as Low birth weight is concerned frequency is not high in gas affected area as this hospital is specifically meant for Gas affected victims.